2019
DOI: 10.1021/acsaem.9b00069
|View full text |Cite
|
Sign up to set email alerts
|

Double-Network Gel-Enabled Uniform Incorporation of Metallic Matrices with Silicon Anodes Realizing Enhanced Lithium Storage

Abstract: Silicon–metal (Si–M) binary materials manifest high tap densities and areal capacities and desirable Li-storage behavior benefiting from metallic matrices and thus have been regarded as promising anodic choices in next-generation Li-ion batteries. To fully realize the hybridization merits, the uniform incorporation of metallic components with silicon is a prerequisite, yet it remains a significant challenge via facile and economic routes. Herein we develop an all-inorganic, double-network, gel-enabled methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…This obtained LIB performance revealed that adding Ag NPs combined with trace ZnO modification can obviously reduce the electrodes' interface polarization, enhance their conductivity, and finally improve their LIB performance. According to the previous reports, metallic components including Ag may act as diffusion barrier to limit the full lithiation of silicon, and the inhibition of its phase transition greatly improves their structural stability and cyclic life. In particular, a comparison between this work and the recently reported excellent Si‐based anodes has been compared in Table S1 in the Supporting Information, indicating the performance for Ag/ZnO‐Si@C‐PCNFs is better than most similar reports on Si/C anodes.…”
Section: Resultsmentioning
confidence: 99%
“…This obtained LIB performance revealed that adding Ag NPs combined with trace ZnO modification can obviously reduce the electrodes' interface polarization, enhance their conductivity, and finally improve their LIB performance. According to the previous reports, metallic components including Ag may act as diffusion barrier to limit the full lithiation of silicon, and the inhibition of its phase transition greatly improves their structural stability and cyclic life. In particular, a comparison between this work and the recently reported excellent Si‐based anodes has been compared in Table S1 in the Supporting Information, indicating the performance for Ag/ZnO‐Si@C‐PCNFs is better than most similar reports on Si/C anodes.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the amorphous nanoparticle, located within the mesopore and attached to the crystalline nanodendrite, can be identified as a silicon fragment by its microarea EDS spectrum with an ultrahigh Si/Sn atomic ratio of 9.8:1 (Figure d). The crystalline/amorphous phase transition of silicon during cycling is further confirmed by Raman spectra, which show a negative shift from 514 cm –1 in uncycled state to 466 cm –1 in delithiated framework (Figure e) …”
mentioning
confidence: 62%
“…Similarly to carbon, metallic matrix can promote electron/ion transport and help maintain electrode integrity of silicon anodes. Besides these common merits, metallic components possess their own properties and peculiar electrochemical mechanisms to boost Si-based lithium storage. Generally, silicon–metal (Si–M) anodes manifest higher tap densities and volumetric energy densities than Si and Si–C ones . Moreover, the concurrent lithium-storage dynamics between active metals (M′ = Ge, Sn, Sb, etc.)…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Metal and metal oxide as other interface layers to improve the electrochemical performance for Si‐based anode have also been investigated. [ 291 ] Some metals such as Mg, [ 292 ] Al, [ 293 ] Ti, [ 294 ] Fe, [ 295 ] Ni, [ 296 ] Cu, [ 297 ] Zn, [ 298 ] Ge, [ 299 ] Ag, [ 300 ] and alloy [ 301 ] are applied to fabricate Si‐based anode due to their excellent conductivity and ductility. Wu et al designed 3D Sn–Ni alloy frameworks to in situ immobilize the commercial Si particles via the gel‐reduction route to boost lithium‐storage performance of silicon anodes.…”
Section: Designing Protective and Conductive Phases For Si Anodementioning
confidence: 99%